Dual role of G-runs and hnRNP F in the regulation of a mutation-activated pseudoexon in the fibrinogen gamma-chain transcript. - Valeria Rimoldi (Public Library of Science (PLoS), 2013)
Most pathological pseudoexon inclusion events originate from single activating mutations, suggesting that many intronic sequences are on the verge of becoming exons. However, the precise mechanisms controlling pseudoexon definition are still largely unexplored. Here, we investigated the cis-acting elements and trans-acting regulatory factors contributing to the regulation of a previously described fibrinogen gamma-chain (FGG) pseudoexon, which is activated by a deep-intronic mutation (IVS6-320A>T). This pseudoexon contains several G-run elements, which may be bound by heterogeneous nuclear ribonucleoproteins (hnRNPs) F and H. To explore the effect of these proteins on FGG pseudoexon inclusion, both silencing and overexpression experiments were performed in eukaryotic cells. While hnRNP H did not significantly affect pseudoexon splicing, hnRNP F promoted pseudoexon inclusion, indicating that these two proteins have only partially redundant functions. To verify the binding of hnRNP F and the possible involvement of other trans-acting splicing modulators, pulldown experiments were performed on the region of the pseudoexon characterized by both a G-run and enrichment for exonic splicing enhancers. This 25-bp-long region strongly binds hnRNP F/H and weakly interacts with Serine/Arginine-rich protein 40, which however was demonstrated to be dispensable for FGG pseudoexon inclusion in overexpression experiments. Deletion analysis, besides confirming the splicing-promoting role of the G-run within this 25-bp region, demonstrated that two additional hnRNP F binding sites might instead function as silencer elements. Taken together, our results indicate a major role of hnRNP F in regulating FGG pseudoexon inclusion, and strengthen the notion that G-runs may function either as splicing enhancers or silencers of the same exon.